The critical success factors for landscape management of operations on sustainable urban drainage system (SuDS) projects - Spolander, Robyn Anne (Department of Construction Economics and Management, 2023)
Population explosion and urbanization are the most significant reasons for increasing pressure on the earth's natural resources, particularly water. Historically, water services have been supplied and discharged through a network of piped infrastructure and hardened surfaces with the main objectives of efficiency and risk management. Separation in service provision of water resources has proven operationally unsustainable, with increasing negative impacts on the environment. New approaches have been sought to mitigate these impacts through a new paradigm in urban stormwater management, referred to as Sustainable Urban Drainage Systems (SuDS), which describes a strategic sustainable approach to the management of stormwater quality and quantity. Various typologies are used individually or in configurations to form a treatment train with engineered and landscape infrastructure components that are mutually supportive. Much research has been done on the design and implementation phases of this infrastructure, but the literature reveals a less detailed understanding of the intricate management and operational aspects of SuDS. This case study considers the Critical Success Factors in the management and maintenance of SuDS on landscape projects during the operational phase, that contribute to optimal functioning of these complex ecological systems for the benefits of ecosystem goods and services and quality of life for all. This research design has been couched in the pragmatic paradigm which considers the problem at the heart of the research, approaching research from a qualitative perspective. To fulfill the research objectives, a critical literature review was conducted, and a single case study research methodology used to investigate this phenomenon, located at Intaka Island, Century City, Cape Town that has been operationally successful for over two decades. Qualitative thematic analysis was carried out through empirical inquiry on the management and maintenance approaches followed. The research design included data collection of from a variety of sources. These were then expressed through rich descriptive text which was, analysed, and interpreted through a process of triangulation, leading to the establishment of emergent themes and the assertions of four prominent Critical Success Factors, namely: strategic vision, culture of learning, clearly defined management objectives and adaptive management. From this, conclusions are drawn, and recommendations made.